PENYELESAIAN SENGKETA PERTANAHAN MELALUI PERADILAN ADAT DI DESA BLANG RAJA KECAMATAN BABAHROT KABUPATEN ACEH BARAT DAYA - Susi Maila; Basri Basri (Jurist Argumentum: Pemikiran Intelektual Hukum, 2023)
Land disputes are differences in values, interests, opinions and a perception between individuals regarding ownership status. The customary court in Blang Raja Village, Babahrot District, Southwest Aceh Regency, in handling land disputes did not fulfill the elements of the applicable regulations, namely the implementation was not in accordance with the stages as stipulated in the provisions of Qanun Aceh Number 9 of 2008 concerning the Development of Customary and Customary Life. Writing in this journal aims to examine the mechanisms for resolving land disputes through customary justice in Blang Raja Village and what are the obstacles in implementing land dispute resolution through customary justice in Blang Raja Village. The method used in this research is empirical juridical, collecting data in the field through interviews with respondents and informants, as well as documentation of activities in the field. The results of this study indicate that the mechanism for resolving land disputes through customary justice in Blang Raja Village is carried out by way of deliberation, consensus or kinship and by asking for help from a third party acting as a mediator. As for the customary justice in Blang Raja Village, it is still ineffective in resolving disputes so that there are obstacles in the process of implementing land dispute resolution in Blang Raja Village at this time, where the absence of the disputing parties is one of the reasons, so that each party disputing defending his own opinion, one party objected to the peace decision, lack of understanding of gampong officials regarding customary justice.